Семен Виноградов - Краснова Вера Владимировна (Удмуртия, 2014)
Экземпляры: ф.12 (2019) / Инвентарный номер: 55308 / Цена: / Сис.шифр: К85.143(2Рос=Удм) / Авт.знак: В 49 / ГРНТИ: 18.31.31 / ББК: 85.143(2=664.1)